1998
DOI: 10.1074/jbc.273.16.9976
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of RNA Strand Displacement Synthesis by Moloney Murine Leukemia Virus Reverse Transcriptase

Abstract: The RNase H activity of reverse transcriptase (RT) is presumably required to cleave the RNA genome following minus strand synthesis to free the DNA for use as a template during plus strand synthesis. However, since RNA degradation by RNase H appears to generate RNA fragments too large to spontaneously dissociate from the minus strand, we have investigated the possibility that RNA displacement by RT during plus strand synthesis contributes to the removal of RNA fragments. By using an RNase H ؊ mutant of Moloney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
63
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 64 publications
3
63
1
Order By: Relevance
“…Recently, a study using murine leukemia virus RT showed that the wild-type enzyme supports a greater amount of synthesis on a DNA template with an annealed downstream RNA than the RNase Hminus mutant (22). This result indicates that the RT with RNase H activity has a higher efficiency for the removal of downstream RNA.…”
mentioning
confidence: 80%
“…Recently, a study using murine leukemia virus RT showed that the wild-type enzyme supports a greater amount of synthesis on a DNA template with an annealed downstream RNA than the RNase Hminus mutant (22). This result indicates that the RT with RNase H activity has a higher efficiency for the removal of downstream RNA.…”
mentioning
confidence: 80%
“…SP6S1 (5Ј-AGCTATTTAGGTGACACTA-TAGAATACGCATG-3Ј) and SP6S2 (5Ј-CGTATTCTATAGTGTCACCT-AAAT-3Ј) were used to insert an SP6 promoter into M13INT. Amplification primers T7M13 and TermM13, used to generate M13LTR1, have been described (22). Construction of plasmids pGEMLTR2 and M13LTR2 has been described previously (22); pGEMLTR1 was similarly generated but contains a 738-bp insert from the Mo-MLV LTR (genome position 7758 -8332 joined to 69 -231 (23)) that, in addition to downstream sequences, includes the PPT and 68 nt of upstream sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Amplification primers T7M13 and TermM13, used to generate M13LTR1, have been described (22). Construction of plasmids pGEMLTR2 and M13LTR2 has been described previously (22); pGEMLTR1 was similarly generated but contains a 738-bp insert from the Mo-MLV LTR (genome position 7758 -8332 joined to 69 -231 (23)) that, in addition to downstream sequences, includes the PPT and 68 nt of upstream sequence. M13LTR1 was constructed by cloning a polymerase chain reaction-amplified 782-bp region of pGEMLTR1, including the LTR insert, into M13mp7 DNA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations